New antibacterial agents: Hybrid bioisoster derivatives as potential E. coli FabH inhibitors. Issue 16 (15th August 2016) - Segretti, Natanael D.; Serafim, Ricardo A.M.; Segretti, Mariana C.F.; Miyata, Marcelo; Coelho, Fernando R.; Augusto, Ohara; Ferreira, Elizabeth I.
Graphical abstract: Highlights: Sulfonylhydrazone bioisosters and furoxan hybrids have been designed against Escherichia coli . One of the compounds designed by molecular hybridization showed to be highly active and non-cytotoxic in Vero cells. Molecular docking supported FabH as the macromolecular target for the antimicrobial action. Abstract: The development of resistance to antibiotics by microorganisms is a major problem for the treatment of bacterial infections worldwide, and therefore, it is imperative to study new scaffolds that are potentially useful in the development of new antibiotics. In this regard, we propose the design, synthesis and biological evaluation of hybrid sulfonylhydrazone bioisosters/furoxans with potential antibacterial ( Escherichia coli ) activity. The most active compound of the series, ( E )-3-methyl-4-((2-tosylhydrazono)methyl)-1, 2, 5-oxadiazole 2-oxide, with a MIC = 0.36 μM, was not cytotoxic when tested on Vero cells (IC50 >100 μM). To complement the in vitro screening, we also studied the interaction of the test compounds with β-ketoacyl acyl carrier protein synthase (FabH), the target for the parent compounds, and we observed three important hydrogen-bonding interactions with two important active site residues in the catalytic site of the enzyme, providing complementary evidence to support the target of the new hybrid molecules.